New Insight in HDACs: Potential Therapeutic Targets for the Treatment of Atherosclerosis - Luan, Yi; Liu, Hui; Luan, Ying; Yang, Yang; Yang, Jing; Ren, Kai-Di (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) features include progressive hardening and reduced elasticity of arteries. AS is the leading cause of morbidity and mortality. An increasing amount of evidence showed that epigenetic modifications on genes serve are a main cause of several diseases, including AS. Histone deacetylases (HDACs) promote the deacetylation at lysine residues, thereby condensing the chromatin structures and further inhibiting the transcription of downstream genes. HDACs widely affect various physiological and pathological processes through transcriptional regulation or deacetylation of other non-histone proteins. In recent years, the role of HDACs in vascular systems has been revealed, and their effects on atherosclerosis have been widely reported. In this review, we discuss the members of HDACs in vascular systems, determine the diverse roles of HDACs in AS, and reveal the effects of HDAC inhibitors on AS progression. We provide new insights into the potential of HDAC inhibitors as drugs for AS treatment.